Diagnosis and Successful Surgical Management of Concomitant Granulosa Cell Tumor and Pyometra in a Beagle Dog: A Case Report - Kumar, Sushil; Singh, Kiran; Biswas, Newton (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Ovarian tumor arises from the uncontrolled and abnormal proliferation of cells located in the ovary. It mostly affects older female dogs, especially the unspayed ones. The overall prevalence of ovarian tumours is 0.5% to 1.2%, but is as high as 6.25% in intact female dogs (Bhoi et al., 2022). Based on their origin, canine ovarian tumors are categorized into three groups: germ cell tumors, sex cord-stromal tumors, and epithelial cell tumors (Kennedy 1998). Granulosa cell tumors (GCTs) that originate from sex cord stromal cells are one of the most commonly reported neoplasms in canine ovary. This accounts for about 50% of all ovarian tumors (Diez-bru et al., 1998). GCTs cause increase in ovarian hormone levels such as estradiol, progesterone and inhibin-A (Pluhar et al., 1995). This increased hormonal secretion leads to development of clinical symptoms like persistent estrus, vulvar swelling with discharge, slow movement and especially persistent abdominal enlargement. It can also cause nymphomania, virilization, hyperadrenocorticism, alopecia and sometimes complicated mammary carcinoma (Headley et al., 2006; Buijtels et al., 2010; Chung et al., 2013). GCTs in bitches have various microscopic appearances, such as follicular, cystic or poly cystic, and solid. The more important and prominent pattern in some GCT is follicular solid sheet, cords, trabecular, or nests (Buijtels et al., 2010). Histologically, granulosa cells in this tumor are similar to normal granulosa cells and are often arranged like normal Graafian follicles. ET-1 (endothelin) and ET-A (endothelin-A receptor) are over expressed in canine ovarian tumours, suggesting a potential role of these two molecules in canine ovarian carcinogenesis (Borzacchiello et al., 2010). Diagnostic tools like radiography and ultrasonography play vital role in early identification of tumors like GCTs. The present case report records diagnosis and surgical management of ovarian tumour (Granulosa Cell Tumour) and pyometra in a ten year old Beagle dog.